(untitled) (INNOVATIVE ECONOMY, 2025)
Fedoryshyna L.M., Makartetska V.S., Rohozha A.O., Havrysh A.V. MANIFESTATIONS OF INEQUALITY IN THE ACADEMIC ENVIRONMENT AND ON THE LABOUR MARKET AND COMMUNICATIVE TECHNOLOGIES FOR OVERCOMING IT Purpose. The aim of the article is to investigate the manifestations of inequality in the academic environment and on the labour market, to form the causes of its occurrence and possible ways to overcome it, as well as outlining the role of communication technologies in this process. Methodology of research. The following research methods were used to achieve the set goal, in particular: analysis, monographic, abstract and logical, generalization ‒ to consider the essence of inequality and its types, to formulate the causes of inequality in the academic environment and on the labour market, possible ways to eliminate it; survey using the Google form ‒ to identify the opinions of higher education applicants regarding the manifestations of inequality in the academic environment and employees regarding the manifestations of inequality in the labour market; tabular ‒ to systematize and better visualize the results of the conducted study. Findings. The essence and types of inequality is considered. The causes of inequality in the academic environment and on the labour market is generalized. The reasons for its appearance in the academic environment include unequal access to quality education, financial barriers, stereotypes and prejudices, inequality in academic opportunities, academic nepotism and favouritism, differences in digital competencies, and in the labour market ‒ the educational gap, gender inequality, stigmatization of certain social groups, ageism, unequal access to vacancies, information asymmetry, outsourcing, etc. A survey of education seekers is conducted regarding manifestations of inequality in the academic environment, which made it possible to establish that the seekers we surveyed mostly do not encounter its manifestations in their own educational institutions and the majority indicate that all students have equal opportunities. In contrast, the results of a survey of employees regarding manifestations of inequality in the labour market showed that more than half of those surveyed had encountered them personally, in particular ageism and sexism. Ways to overcome inequality in the academic environment and in the labour market was formed. The role of communication technologies in overcoming inequality is outlined. Originality. The study of manifestations of inequality in the academic environment and on the labour market has received further development, which made it possible to form possible ways to overcome it in modern conditions. Practical value. The results of the conducted research can become the basis for the development of programs to overcome manifestations of inequality in the academic environment and on the labour market, as well as further scientific research in this direction. Key words: inequality, manifestations of inequality, ageism, gender inequality, prejudice, stereotypes, labour market, academic environment, overcoming inequality, communication technologies, digital platforms, digital communications.